Interdependence in the therapeutic compliance of hypertensive older adults during the COVID-19 pandemic - Lopes, Thamyres de Oliveira; Bitencourt, Graziele Ribeiro; Andrade, Angélica Mônica; Silva, Renan Alves; Lopes, Rafael Oliveira Pitta (Revista da Escola de Enfermagem da USP, 2022)
Objective: to analyze stimuli and behaviors related to interdependence and their implications for compliance with the therapeutic regimen of older adults with hypertension during the COVID-19 pandemic. Method: a multiple case, qualitative study, carried out with fifteen older adults treated at a Family Health Strategy unit. A characterization instrument and semi-structured interview were used for data collection. Data were processed in NVivo12, submitted to thematic content analysis, based on Roy’s interdependence mode. Results: the reports seized showed that the family has meaning as a therapeutic support network, as well as health services, neighbors, friends and religious institutions. Two categories emerged: Stimuli and adaptive behaviors related to interdependence in the pandemic: implications for compliance; Ineffective stimuli and behaviors related to interdependence in the pandemic: implications for compliance. Conclusion: adaptive and ineffective behaviors related to interdependence during the adjustment to the new condition of social distancing demonstrate the need for greater professional attention to achieve compliance with treatment.